The Influence of Social Media Use on the Cognitive Abilities of Fifth Grade Students in Science Subjects at SDN 4 Abuan - Putra, I Ketut Dedi Agung Susanto; Luh Candra Mitha Utami (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2023)
This study aims to determine the effect of the application of social media on the cognitive abilities of students in science class V SDN 4 Abuan. This type of research uses quantitative descriptive research with data collection techniques using observation and tests. The population of this study is all students of SDN 4 Abuan odd semester of the 2022/2023 academic year. As a sample in this study, there were 15 grade V students of SDN 4 Abuan in the odd semester of the 2022/2023 academic year. Based on the results of data analysis, it was found that there was a significant influence on the use of social media in learning. The effective time for learning by utilizing social media is as much as 25% of learning and 1 to 3 hours during the learning process both at school and at home